Sistem Pemantauan dan Pengendalian Oksigen Terlarut Berbasis IoT untuk Budidaya Udang Vannamei di Air Payau Menggunakan Long Range Wide Area Network (LoRaWAN) - Safira Firdaus Mujiyanti; Ahmad Radhy; Mia Nilam Cahya; Yus Putri Arum Segar (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2025)
Vannamei shrimp farming in Indonesia is increasing due to its high economic value. Water quality management in aquaculture ponds is crucial to minimize the number of diseases related to poor water quality. One of the water quality parameters in shrimp farming is dissolved oxygen. In this monitoring and control system for dissolved oxygen in brackish water Vannamei shrimp farming based on the Internet of Things (IoT) using the Long Range Wide Area Network (LoRaWAN), measurements of dissolved oxygen levels in cultured water are carried out and displayed in the Android application so that it can be monitored by farmers in real time. When the dissolved oxygen level in the cultured water is more than 5.7 mg/l, the aerator will be OFF, but if the dissolved oxygen level is less than 5.7 mg/l, the aerator will be ON to maintain optimum dissolved oxygen levels for shrimp farming, which is more than 5 mg/l. Dissolved oxygen sensor validation is carried out, resulting in a measurement error correction value of 2.25% and an accuracy level of 97.74%. Based on the test results, this device can monitor dissolved oxygen in real time and operate the control system to maintain levels above the predetermined setpoint of 5 mg/l.